Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Konsumen Pada Toko Alfamart Cabang Setiabudi Pamulang - Munarsih Desma Simatupang Nurmin Arianto (KREATIF : Jurnal Ilmiah Prodi Manajemen Universitas Pamulang, 2022)
The results showed that partially the service quality variable had a significant effect on consumer satisfaction by showing the results of the t-test = 6.450 while t-table = 1.98498 (tcount > ttable) with a significance level of 0.000. Partially, the Promotion variable has a significant effect on Consumer Satisfaction by showing the results of tcount = 2,343 while ttable = 1,98498 (tcount > ttable) with a significance level of 0.000. Simultaneously, the variables of Service Quality and Promotion have a significant effect on customer satisfaction by showing Fcount = 50,612 which is greater than Ftable = 3.09 with a significance of 0.0000. So it can be said that Service Quality and Promotion simultaneously have a significant effect on Consumer Satisfaction at the Alfamart Store, Setiabudi Pamulang Branch. The coefficient of determination obtained is 0.513, it can be concluded that Service Quality (X1) and Promotion (X2) have an effect on Consumer Satisfaction (Y) by 51.30% while the remaining 48.70% is influenced by other factors not tested in this study.